The Growth, Productivity and Quality of Fifteen Accessions of Ceylon Cinnamon at Medium Elevation of Solok, West Sumatera - Erma Suryani; NFN Nurmansyah; Susi Purwiyanti; Otih Rostiana (Buletin Penelitian Tanaman Rempah dan Obat, 2017)
The evaluation of growth, productivity and quality of 15 accessions of Ceylon cinnamon (Cinnamomum zeylanicum Blume) at the medium elevation in Laing Research Installation Solok West Sumatra, has been conducted from January 2007 to April 2013. The experiment was arranged in Randomized Block Design with 15 treatments (accessions) and repeated three times. Parameter observed were plant height, stem diameter, number of branches, bark thickness, bark production, leaf production, oil yield and components of oils. The results showed that, the highest plant height was Czl16 (497.67 cm) and Czl30 (478.33 cm). The largest stem diameter was Czl16 (12.33 cm) followed by Czl15 (11.33 cm) Czl02 (11.00 cm) and Czl29 (11.00 cm). The highest branch number was Czl30 (30.00), Czl15 (29.00), Czl22 (29.00) and Czl35 (28.66). The highest production of dry bark was Czl30 (4,350 g.treeˉ¹) and the lowest one was Czl03 (1,800 g.treeˉ¹). The highest leaf production was Czl15 (18,700 g.treeˉ¹ and Czl16 (18366.67 g.treeˉ¹), and the lowest one was Czl03 (7,633.33 g.treeˉ¹). The highest of oil yield was Czl12 and  Czl30 0.75 %  each  and the lowest one was Czl11 (0.27 %). The highest of  cinnamaldehyde content was Czl35 (61.24 %), followed by Czl22 (59.38 %) and the lowest one was Czl17 (37.78 %). The chemical components of oils of cinnamon bar analyzed by GCMS from Czl35 accession consisted of 51 components and the primary components were cinnamaldehyde 61.29 %, eugenol 6.87 %, β-caryophyllane 6.59 %, cinnamyl acetate 5.61 %, β-phellandrene 4.79 %, dillapiole 3.39 %, benzoic acid 1.82 %, Linalool 1 %, and 43 other components each below 1 %.